Meta-analysis protocol on the effects of cover crops on pool specific soil organic carbon - Fohrafellner, Julia; Zechmeister-Boltenstern, Sophie; Murugan, Rajasekaran; Keiblinger, Katharina; Spiegel, Heide; Valkama, Elena (Elsevier BV, 2023)
Soil organic carbon (SOC) plays an important role in agricultural soils, as it contributes to overall soil health as well as climate change mitigation and adaptation. By conducting a meta-analysis, we aim to quantitatively summarize research studying the effects of cover crops (CC) on SOC pools throughout soil depths in arable cropland. We included global studies located in the climatic zones present in Europe. The pools chosen for this analysis are the particulate organic carbon (POC) and the mineral associated organic carbon (MAOC) and the microbial biomass carbon (MBC). Alongside, we will study the effects of a broad range of moderators, such as pedo-climatic factors, other agricultural management practices and CC characteristics e.g., type. We identified 71 relevant studies from 61 articles, of which mean values for SOC pools, standard deviations and sample sizes for treatments (CC) and controls (no CC) were extracted. To perform the meta-analysis, an effect size will be calculated for each study, which will then be summarized across studies by using weighing procedure. Consequently, this meta-analysis will provide valuable information on the state of knowledge on SOC pool change influenced by CC, corresponding quantitative summary results and the sources of heterogeneity influencing these results. Graphi
Keywords: EJPSOIL; SOC pools; synthesis; Effect size; MAOC; MBC; POC